Molecular aspects of the early stages of elicitation of secondary metabolites in plants - Vasconsuelo, Andrea Anahi (2007)
Plants are a source of commercially important secondary metabolites. Elicitation of plant cells in culture represents a useful biotechnological tool to improve the production of these valuable metabolites. Greater knowledge on the mechanism of elicitation has basic as well as practical implications. This review summarizes molecular information available about the early stages of the elicitation process and the mode of action of elicitors. A description is first provided on the importance of plant secondary metabolism, its induction by elicitation, the elicitor concept and classification, factors affecting elicitation and the mechanisms involved, with a major emphasis on the intracellular transduction systems which mediate the actions of elicitors, namely, elicitor receptors, GTP binding proteins, the Ca2+ messenger system and the PI3K, PLC/IP3-DAG/PKC and adenylyl cyclase/cAMP/PKA pathways, which finally act through mitogen-activated protein kinases (MAPKs) affecting the expression of genes related to the biosynthesis of secondary metabolites. Relevant experimental approaches used to study these topics are also discussed.